2020
DOI: 10.1182/blood-2020-142087
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin Supplementation in Adults with Acute Lymphoblastic Leukemia (ALL) Following Asparaginase Therapy: A Meta-Analysis

Abstract: Background: Aspagarinase is a fundamental component for the treatment of patients with acute lymphoblastic leukemia (ALL). Venous thromboembolism (VTE) is a known complication of asparaginase therapy during treatment for ALL. This is attributed to the depletion of anticoagulants, particularly acquired antithrombin deficiency following asparaginase administration. The incidence of thrombosis following asparaginase is more prevalent in adults versus children and is estimated to be around 5-35 % an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…120 More recently, a 2020 meta-analysis of 8 retrospective studies on AT in patients with ALL found that the risk of VTE was significantly lower in adults with AT therapy versus those without. 13 Guidelines from the Scientific and Standardization Committee of the International Society on Thrombosis and Haemostasis recommend AT therapy for adults with ALL receiving l -asparaginase treatment at a threshold AT level of 50% to 60%, targeting AT concentration in the normal range (80%-120%). 121…”
Section: Additional Patient Populations and Use Cases Where At Therap...mentioning
confidence: 99%
See 3 more Smart Citations
“…120 More recently, a 2020 meta-analysis of 8 retrospective studies on AT in patients with ALL found that the risk of VTE was significantly lower in adults with AT therapy versus those without. 13 Guidelines from the Scientific and Standardization Committee of the International Society on Thrombosis and Haemostasis recommend AT therapy for adults with ALL receiving l -asparaginase treatment at a threshold AT level of 50% to 60%, targeting AT concentration in the normal range (80%-120%). 121…”
Section: Additional Patient Populations and Use Cases Where At Therap...mentioning
confidence: 99%
“…157 Meta-analyses of pooled trials exist, but they have low quality of evidence due to high probability of bias and heterogeneity in the patient populations of the pooled trials, which are variable in participants, severity of condition, treatment regimens, and clinical setting. 13,15,47,48,80,157 Patients and providers would benefit from a large-scale randomized controlled trial with low bias risk that would provide a high level of evidence concerning the effectiveness of AT use and supplementation.…”
Section: Future Outlookmentioning
confidence: 99%
See 2 more Smart Citations